(untitled) (Revista Sistemas de Producción Agroecológicos, 2020)
In this work, the impact of different uses on soil compaction is evaluated, for which the current and current means uses in the area of ​​Puerto Lleras-Meta-Colombia are studied: silvopastoral system (SPP), monoculture (MON), pasture (PS) and secondary forest (SF), a composite sample of 5 points at 20 cm of depth was redirected for each system, we used an experimental design absolutely randomly DIA, because the physical-chemical analyzes of the soil were analyzed under controlled laboratory conditions. The variables that were evaluated were: Organic matter (Walkley and Black), pH (potentiometric), Apparent density, Gravimetric humidity, Volumetric humidity, Real density, Porosity, Water sheet, Volumetric humidity at field capacity, Macroporosity, Resistance to Penetration and texture. To assess the resistance to penetration of each of the systems, the penetrator has also been used. The statistical analysis was carried out by means of the analysis of variance (P<0.01) and the differences between the treatments were analyzed by the Tukey test (P<0.05). The data were run in the Infostat statistical package. The results indicate that the SF, SPS, PS and MON do not present problems of compaction, means by the apparent presence and the resistance to the penetration, the systems of predominance of the sandy ones and therefore are less susceptible to this problem, the system However, there was not a problem of compaction that tends to a macroporosity (M) close to 10% (14.08%). The SPS presented a total ideal, and the FS is a highly water retaining system.